2011
DOI: 10.1103/physreve.83.051106
|View full text |Cite
|
Sign up to set email alerts
|

Particle diode: Rectification of interacting Brownian ratchets

Abstract: Transport of Brownian particles interacting with each other via the Morse potential is investigated in the presence of an ac driving force applied locally at one end of the chain. By using numerical simulations, we find that the system can behave as a particle diode for both overdamped and underdamped cases. For low frequencies, the transport from the free end to the ac acting end is prohibited, while the transport from the ac acting end to the free end is permitted. However, the polarity of the particle diode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recently, it was demonstrated that lattices with spatially dependent driving imply a tunable phase space [17] and enrich the physics of dcs with mechanisms allowing for the creation of traveling density waves [18] and designable patterned particle deposition [19]. All of the above investigations do not focus on particle interactions and indeed most works on interacting ratchets concentrate either on the stochastic or the overdamped deterministic case [20][21][22][23], leaving a gap in the literature concerning the microscopic analysis of interacting (deterministic) ratchets. In this context, a topic of particular interest is the so-called currentreversals [11,17,[24][25][26][27][28], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that lattices with spatially dependent driving imply a tunable phase space [17] and enrich the physics of dcs with mechanisms allowing for the creation of traveling density waves [18] and designable patterned particle deposition [19]. All of the above investigations do not focus on particle interactions and indeed most works on interacting ratchets concentrate either on the stochastic or the overdamped deterministic case [20][21][22][23], leaving a gap in the literature concerning the microscopic analysis of interacting (deterministic) ratchets. In this context, a topic of particular interest is the so-called currentreversals [11,17,[24][25][26][27][28], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the impact of the frequency of oscillating driving force, which is applied at one end of a particle chain, on the mean velocity of Brownian particles interacting with each other via the Morse potential and under an asymmetric periodic potential have been investigated in Ref. [9]. In their work, Ai et al integrated equations of motion for overdamped and underdamped cases by the second-order stochastic Runge-Kutta method.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[4] On the other hand, entropic barriers are used to separate dispersed particles from a suspension fluid. DNA separation, [5,6] particle diode, [3,[7][8][9] and separation of particles according to their sizes [10][11][12] are common examples of utilizing entropic barriers in technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite often considered as being of single particle character, ratchets can experience a profound impact by interactions [11][12][13][14][15][16][17][18][19][20]. Specifically, interactions can accelerate single particle transport [15][16][17][18][19]21], enhance their controllability [15][16][17][18][19] and lead to one or multiple reversals [21][22][23] of the transport direction which could be observed experimentally e.g.…”
Section: Introductionmentioning
confidence: 99%